Psychotropic prescribing in HIV - E Reid; C Orrell; K Stoloff; J Joska (Southern African Journal of HIV Medicine, 2012)
Psychiatric disorders frequently co-occur with HIV, as preceding conditions or consequent to HIV infection. This potentially compromises HIV diagnosis and antiretroviral (ARV) treatment adherence. We provide a brief guide to the diagnosis and treatment of common mental disorders in people living with HIV/AIDS, including: prescribing psychotropics in HIV; neuropsychiatric side-effects of ARVs and other medications commonly prescribed in HIV; and the diagnosis and treatment of depression, anxiety, psychosis, agitation, sleep disturbance, pain, and mania. Psychotropic treatments recommended were drawn primarily from those available in the public sector of South Africa.